2021
DOI: 10.1016/j.hroo.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing mechanically sensed atrial tracking in patients with atrioventricular-synchronous leadless pacemakers: A single-center experience

Abstract: Background Atrioventricular (AV)-synchronous single-chamber leadless pacing using a mechanical atrial sensing algorithm produced high AV synchrony in clinical trials, but clinical practice experience with these devices has not yet been described. Objective To describe pacing outcomes and programming changes with AV-synchronous leadless pacemakers in clinical practice. Methods Consecutive patients without persistent atrial fibrillation who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
3
15
0
1
Order By: Relevance
“…greater than 70% AV synchrony. 20 AF was present in 26% of their study sample, and a higher VP burden was associated with lower AV synchrony similar to our results. It makes intuitive sense that when patients are in AF, the ability of the device to sense atrial mechanical activity will be unreliable.…”
Section: F I G U R E 3 (See Caption On Next Page)supporting
confidence: 90%
See 2 more Smart Citations
“…greater than 70% AV synchrony. 20 AF was present in 26% of their study sample, and a higher VP burden was associated with lower AV synchrony similar to our results. It makes intuitive sense that when patients are in AF, the ability of the device to sense atrial mechanical activity will be unreliable.…”
Section: F I G U R E 3 (See Caption On Next Page)supporting
confidence: 90%
“…16,17 Apart from a recent report by Arps et al and a case series reporting troubleshooting scenarios, data regarding the realworld experience of this novel system is lacking. [18][19][20] We sought to define the characteristics of patients undergoing Micra TM -AV implants at the Mayo Clinic, common troubleshooting issues, and the implant outcomes to understand appropriate patient selection and management strategies in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, their data confirms and is in line with recent reports, 8,9 that the success in achieving AV synchrony in a real-world setting may be lower than the MARVEL 2 clinical trial. The results also emphasize the importance of active programming changes which can significantly improve AV synchrony following an optimization postimplantation.…”
supporting
confidence: 88%
“…Critical programming changes made by performing a manual atrial mechanical (MAM) test while disabling the features that automatically affect these include adjusting the PVAB, A3/A4 windows, and A3/A4 thresholds, and turning off the AV conduction mode (VVI+) in those with complete heart block and escape >40 bpm. The authors and others 8,9 have identified helpful examples of troubleshooting these interval timings and thresholds for optimizing AV synchrony, which an implanter must be familiar with to successfully manage patients with leadless AV synchronous devices. Critically, while performing a MAM test, a key prerequisite for successful interpretation of device tracings is the inclusion of an optimal electrocardiogram tracing.…”
mentioning
confidence: 99%